1977
DOI: 10.1128/jvi.21.3.1196-1204.1977
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the defective genes in three mutant groups of influenza virus

Abstract: Seven complementation-recombination groups of temperature-sensitive (ts) influenza WSN virus mutants have been previously isolated. Recently two of these groups (IV and VI) were shown to possess defects in the neuraminidase and the hemagglutinin gene, respectively, and two groups (I and III) were reported to have defects in the P3 and P1 proteins which are required for complementary RNA synthesis. In this communication we report on the defects in the remaining three mutant groups. Wild-type (ts+) recombinants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

1978
1978
2007
2007

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…Since the influenza virus genome consists of eight-segmented and singlestranded RNAs, we detected eight segments of newly synthesized RNAs. The electrophoretic mobility of these RNAs synthesized in the presence of IREF-1 was similar to that of the virus genome RNAs prepared from purified virions (data not shown) and that of RNAs synthesized in the presence of the ApG dinucleotide primer complementary to the nucleotide positions 1 and 2 of the 3 0 -terminus of vRNA (lane 5, and see Ritchey and Palese, 1977;Honda et al, 1986). To determine the polarity of newly synthesized RNA, the RNA possibly synthesized from segment 8 was excised from the gel, and the isolated RNA was then digested with RNase T1.…”
Section: Purification and Characterization Of Iref-1supporting
confidence: 69%
See 2 more Smart Citations
“…Since the influenza virus genome consists of eight-segmented and singlestranded RNAs, we detected eight segments of newly synthesized RNAs. The electrophoretic mobility of these RNAs synthesized in the presence of IREF-1 was similar to that of the virus genome RNAs prepared from purified virions (data not shown) and that of RNAs synthesized in the presence of the ApG dinucleotide primer complementary to the nucleotide positions 1 and 2 of the 3 0 -terminus of vRNA (lane 5, and see Ritchey and Palese, 1977;Honda et al, 1986). To determine the polarity of newly synthesized RNA, the RNA possibly synthesized from segment 8 was excised from the gel, and the isolated RNA was then digested with RNase T1.…”
Section: Purification and Characterization Of Iref-1supporting
confidence: 69%
“…MCM interacted with the viral RNA polymerase through its contact with PA ( Figure 4). Previous genetic analyses suggested that PA participates in the replication process, although its precise role had not been well established (Sugiura et al, 1975;Ritchey and Palese, 1977;Kawaguchi et al, 2005). Recently, it has been reported that the influenza virus vRNP interacts with nucleosomes (Garcia-Robles et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MDBK cells were infected with WSN or ts51 at 32ЊC (lanes 3, 4, 7, and 8) or at 39.5ЊC (lanes 1, 2, 5, and 6). Cells were labeled with32 P i or [ 35 S]methionine at early times (2 to 5 h [lanes 1, 3, 5, and 7]) or at late times (6 to 8 h [lanes 2, 4, 6, and 8]) and analyzed on an SDS-PAGE gel containing 12% acrylamide. M1 and NP are indicated.…”
mentioning
confidence: 99%
“…Membrane (M) protein, which constitutes about 40% of the total amount of virion proteins, forms the internal membrane of a virion. The exact function of M protein in the reproduction of orthomyxoviruses is not yet clear, although results of studies on temperature-sensitive mutants confirm that this protein participates in the late stages of virion morphogenesis (14). Carroll and Wagner (3) recently showed for a vesicular stomatitis virus model that when M protein isolated from virions was added to a system containing vesicular stomatitis virus ribonucleoprotein (RNP), the transcriptase activity was decreased by approximately 40%.…”
mentioning
confidence: 99%